Author Correction: The nature of spin excitations in the one-third magnetization plateau phase of Ba3CoSb2O9 - Y. Kamiya (Nature Portfolio, 2018)
The original version of this Article omitted the following from the Acknowledgements: ‘J. Ma’s primary affiliation is Shanghai Jiao Tong University.’ This has been corrected in both the PDF and HTML versions of the Article.